Major Grass Pollen Allergen Components and Cross-Reactive Carbohydrate Determinants in Mugwort-Sensitized Child Patients With Allergic Respiratory Disease in Western China - Liao, Chenxi; Hou, Xiangqing; Wu, Liting; Luo, Wenting; Zhang, Hong; Sun, Xin; Yu, Yongmei; Zhang, Xiaohua Douglas; Sun, Baoqing (Frontiers in Pediatrics, 2022)
Mugwort is a common pollen allergen in western China, this study aimed to investigate the patterns of molecular sensitization to major grass pollen allergens (mugwort, ragweed, bermuda grass and timothy grass) and cross-reactive carbohydrate determinants (CCD) in children who were sensitized to mugwort in western China. Serum specific IgE (sIgE) of major allergen components and CCD were detected among 121 mugwort SPT-positive children via the EUROBlotMaster system if the mugwort-sIgE was positive (MSP). CCD inhibition test was further performed on the serum of patients with positive CCD-sIgE. Latent class analysis was used to identify the patterns of potential sensitization to major grass pollen allergens. A total of 100 patients with mugwort-sIgE positive (MSP), and 52.0%, 41.0%, 31.0% of them were positive to Art v 1, Art v 3, Art v 4, respectively. An optimal model with 3 latent classes was determined using grass pollen allergens, components and CCD. The sensitization patterns can be summarized as (1) MSP and co-sensitized to ragweed, bermuda grass, timothy grass (23.74%); (2) MSP and co-sensitized to Art v 1 (54.08%); (3) MSP and co-sensitized to Art v 4, Cyn d 12, Phl p 12 (22.18%). Additionally, CCD sIgE levels had a significant positive correlation with ragweed, bermuda grass and timothy grass (P < 0.05), and CCD-Inhibitor can highly inhibit the above allergens sIgE. Our findings suggest that Art v 4 was the typical cross-reaction component of mugwort which is co-sensitized to Phl p 12 and Cyn d 12. A wide cross-reaction among ragweed, bermuda grass and timothy grass caused by CCD was observed.